ANALISIS PERILAKU SOSIAL MASYARAKAT DUSUN PLOSOREJO DESA KEMADUH KAB. NGANJUK DALAM TRADISI YASINAN DAN TAHLILAN (Study Deskriptif Melalui Pendekatan Teori Pertukaran Sosial) - Muhammad Diak Udin (Institut Agama Islam Tribakti (IAIT) Kediri, 2015)
This Small Reasarch is intended to describe the social behavior of the people in the village Plosorejo at yasinan and tahlilan tradition using social exchange theory approach. Social exchange theory is part of interpersonal communication theory that describes how a person lives and enter into a social interaction by considering the consequences derived from the interpersonal interaction. Social exchange theory predicts that the value of a relationship affects the end result (outcome) if people would continue a relationship or end it. A positive relationship can usually be expected to survive, while a negative relationship may be over.Based on this Small Research, the authors can categorize the behavior of people into two groups: First; some people still preserve the tradition of yasinan and tahlilan that in terms of social exchange theory is called the relationship. It means that people feel that there is a balance between sacrifice and awards received. Second; some people are not satisfied with what happened in the tradition of yasinan and tahlilan. This reactions is evidenced by many people who prefer ignore and do not follow. Seen from the perspective of social exchange theory, social behavior at Plosorejo village is the result of an imbalance only between sacrifice and awards received.